Programmed instructional materials on the clausal modifiers of nouns for third year - Labio, Aida C. (1974)
This programmed instructional material on Clausal Modifiers of Nouns is a modest attempt to meet the need for individualized instruction and the need to reduce education costs. It is also an application of research on newer techniques and educational media to improve the efficiency of the teaching-learning process.